2021
DOI: 10.1038/s41598-021-99812-w
|View full text |Cite
|
Sign up to set email alerts
|

Parental methyl-enhanced diet and in ovo corticosterone affect first generation Japanese quail (Coturnix japonica) development, behaviour and stress response

Abstract: The role of maternal investment in avian offspring has considerable life history implications on production traits and therefore potential for the poultry industry. A first generation (G1) of Japanese quail (Coturnix japonica) were bred from a 2 × 2 factorial design. Parents were fed either a control or methyl-enhanced (HiBET) diet, and their eggs were treated with a vehicle or corticosterone injection during day 5 of incubation. A subset of G1 birds were subjected to an open field trial (OFT) and capture-rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Steroid analysis was performed by targeted liquid chromatographytandem mass spectrometry (LC-MS/MS), following extraction of samples through automated supported liquid extraction (SLE) on an Extrahera liquid handling robot (Biotage, Uppsala, Sweden), adapted fromBoulton et al (2021). The method has an intra-and interassay coefficient variation between 4.9% and 7.2% for the five steroids measured: E2, aldosterone, testosterone, androstenedione and progesterone.…”
mentioning
confidence: 99%
“…Steroid analysis was performed by targeted liquid chromatographytandem mass spectrometry (LC-MS/MS), following extraction of samples through automated supported liquid extraction (SLE) on an Extrahera liquid handling robot (Biotage, Uppsala, Sweden), adapted fromBoulton et al (2021). The method has an intra-and interassay coefficient variation between 4.9% and 7.2% for the five steroids measured: E2, aldosterone, testosterone, androstenedione and progesterone.…”
mentioning
confidence: 99%
“…In particular, in ovo feeding has been reported for improving coturniculture production. In this respect, potential increases in growth-related endocrine activity of various compounds, including estradiol benzoate, estrogen, and corticosterone, during the quail’s embryo development have been well documented [ 8 , 24 , 25 ]. Furthermore, numerous studies have reported the usefulness of early feeding of the quail’s embryo with several exogenous molecules, such as vitamins, amino acids, and plant extracts [ 11 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phenotypic traits displayed by offspring as they transition into adulthood largely results from a complex interaction between genetic and maternal factors encountered during embryonic development ( Groothuis et al, 2019 ; Peixoto et al, 2020a , b ; Boulton et al, 2021 ). These maternal factors are a result of the environment encountered by a mother at the time of gestation, or in oviparous species, during egg formation.…”
Section: Introductionmentioning
confidence: 99%
“…These maternal factors are a result of the environment encountered by a mother at the time of gestation, or in oviparous species, during egg formation. In avian species, maternally derived differences in offspring phenotypes are likely mediated through hormonal or nutritional alterations to the composition of the egg during formation ( Henriksen et al, 2011b ; Angove and Forder, 2020 ; Boulton et al, 2021 ). A range of factors can influence the egg composition, including but not limited to; environmental ( Sheriff et al, 2017 ), nutritional status ( Gatford et al, 2018 ), and stress ( Gatford et al, 2018 ; Angove and Forder, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation